Bilateral corneal perforation and iris prolapse as a complication non-peripheral ulcerative keratitis in a patient with fulminant Granulomatosis with Polyangiitis. A case Report. (2020)
Granulomatosis with polyangiitis (GPA) (formerly known as Wegener´s granulomatosis) is a systemic necrotizing vasculitis belonging to a heterogeneous group of systemic anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis which affects small and medium-sized blood vessels [1, 2]. The annual incidence of GPA has been estimated to be 8 to 10 million, has a peak age of onset of 64 to 75 years [3], and the frequency of presentation in female and male individuals is similar [4]. Constitutional signs like fever, asthenia, and weight loss are frequent (50%) but non-specific. Ear, nose, and throat signs (crusting rhinorrhea, sinusitis, chronic otitis, or damage of the facial cartilage) are present in 70 to 100% of cases at diagnosis [5]. Lung involvement, characterized by alveolar hemorrhage or parenchymatous nodules, affects 50 to 90% of patients [4]. The focal segmental necrotizing glomerulonephritis is the most frequent renal involvement in 40 to 100% of cases [6]. Involvement of the nervous system, the central nervous system, the pachymeninges, the heart, the pericardium, and the gastrointestinal system are less frequent, observed in a range of 5 to 40% of cases [1].